Associations of General Self-Efficacy and Digital Health Literacy with Self-Management and Intention to Use Digital Health Services Among Adults Aged 50 Years and Older with Chronic Disease: A Cross-Sectional Study - Soylar, Pınar; Aşan, Gülsüm; Ulaş Kadıoğlu, Bircan (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
Background: Digital health literacy and general self-efficacy may influence chronic disease self-management and the intention to use digital health services among adults aged 50 years and older. This study examined the associations of these factors with self-management and intention to use digital health services. Methods: This cross-sectional descriptive study included 230 adults aged 50 years and older with chronic disease. Participants attended the outpatient clinics of a district state hospital in southeastern Türkiye. Data were collected using the Digital Health Literacy Scale, the Chronic Disease Self-Management Scale, and the General Self-Efficacy Scale. Descriptive statistics, correlation analysis, and hierarchical regression analyses were performed. Results: The mean age of participants was 59.82 ± 7.53 years, and 58.7% were female. Hierarchical regression analyses showed that general self-efficacy was independently associated with both chronic disease self-management (B = 0.015, 95% CI [0.007, 0.023], β = 0.234, p < 0.001) and the use of digital health services (B = 0.052, 95% CI [0.005, 0.100], β = 0.289, p = 0.005). In contrast, digital health literacy was not independently associated with chronic disease self-management (B = −0.083, 95% CI [−0.173, 0.008], β = −0.118, p = 0.174) or intention to use digital health services (B = 0.131, 95% CI: −0.123 to 0.385, β = 0.083, p = 0.311). The addition of digital health literacy and general self-efficacy significantly improved the explanatory power of the regression models for chronic disease self-management (ΔR2 = 0.067, p < 0.001) and intention to use digital health services (ΔR2 = 0.117, p < 0.001). Conclusions: The findings suggest that general self-efficacy may play a more prominent role than digital health literacy in supporting self-management and digital health service use among adults aged 50 years and older with chronic disease. Interventions aiming to support digital health engagement may benefit from incorporating strategies to strengthen self-efficacy alongside digital skills development. Due to the cross-sectional design, causal inferences cannot be drawn. © 2026 by the authors.
Keywords: Adults Aged 50 Years And Older; Chronic Disease; Digital Health Literacy; General Self-Efficacy; Self-Management